2011
DOI: 10.5539/ijc.v3n3p56
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Study of Dye Water Using Poly Vinyl Alcohol Coated Carbon Black as an Effective and Low Cost Adsorbent

Abstract: The aim of the research is to determine the efficacy of using Poly vinyl alcohol (PVA) coated carbon black to treat wastewater having low dye concentration. The effect of pH, conc. and dose on the adsorption isotherm were studied. Studies conducted to assess the ability of PVA coated carbon black to adsorb dye from wastewater was found to be as an much effective adsorbent. Batch kinetic and isotherm experiment were conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
(6 reference statements)
3
6
0
Order By: Relevance
“…So Nano ZnO at 700 O C corrosion inhibitor has the highest corrosion resistance compared to the other corrosion inhibitors used. Also, it is clear that as the temperature increases, the inhibition effect of the coating increases in agreement with [36][37][38] where the Icorr value decrement means the inhibitor concentration increment. The decrease in I corr value indicates that decrease in flow of electrons, i.e., corrosion is supressed on the specimen.…”
Section: Electrochemical Resultssupporting
confidence: 73%
“…So Nano ZnO at 700 O C corrosion inhibitor has the highest corrosion resistance compared to the other corrosion inhibitors used. Also, it is clear that as the temperature increases, the inhibition effect of the coating increases in agreement with [36][37][38] where the Icorr value decrement means the inhibitor concentration increment. The decrease in I corr value indicates that decrease in flow of electrons, i.e., corrosion is supressed on the specimen.…”
Section: Electrochemical Resultssupporting
confidence: 73%
“…The use of carbon black in adsorbing dyes from wastewater has been reported and it was shown that poly(vinyl alcohol) coated carbon black has the ability to remedy water with considerable dye concentrations [10]. The same study also revealed that the kinetics of adsorption best fit the Langmuir and Freundlich isotherms.…”
Section: Introductionsupporting
confidence: 51%
“…Adsorption is one of the most effective physical processes for the removal of textile effluents [11]. Many adsorbing materials have been tested to lower the dye concentration from aqueous solutions, such as activated carbon, rice husk, silica, chitin, fly ash, saw dust, bagasse pith, and orange peel [12]. Application of natural adsorbents has received much attention for the adsorption of various pollutants from aqueous medium.…”
Section: Introductionmentioning
confidence: 99%